Algae - Keung Wong, Yee (IntechOpen, 2019)
This Edited Volume "Algae" is a collection of reviewed and relevant research chapters, offering a comprehensive overview of recent developments in the field of Agricultural and Biological Sciences. The book comprises single chapters authored by various researchers and edited by an expert active in the Agricultural and Biological Sciences research area. All chapters are complete in itself but united under a common research study topic. This publication aims at providing a thorough overview of the latest research efforts by international authors on Agricultural and Biological Sciences, and open new possible research paths for further novel developments.